Multiple pathological fractures and delayed union associated with lead exposure in a German Shepherd Dog. Issue 10 (October 2015) - Cole, G; Weigel, J; Headrick, A; Adams, W; Biskup, J
<x xml:space="preserve">Abstract</x> Case report An 8‐year‐old 40.8‐kg intact male German Shepherd Dog was evaluated for bilateral antebrachial fractures. Radiographs revealed osteopenia and comminuted proximal diaphyseal fractures of the left radius and ulna, and proximal articular fracture of the right ulna. A dual energy X‐ray absorptiometry scan confirmed decreased bone mineral density. Bone mineral analysis collected at the time of definitive surgical repair demonstrated high lead concentration. Analysis further demonstrated normal bone calcium and phosphorus concentrations. Serum lead concentration was normal. The left radial and ulnar fractures were surgically stabilised with an external fixator. The right ulnar fracture was splinted. The left antebrachial fractures were palpably unstable at 12 weeks after surgery. Moderate callus formation and incomplete bone union were present at 17 weeks postoperatively. The dog was re‐presented 15 months later for right metacarpal and left metatarsal fractures, which were managed conservatively. Complete bone union of the right radial and ulnar fractures was not present at that time. Conclusion Excessive lead accumulation in bone should be considered as a differential diagnosis for increased susceptibility to pathologic fracture and delayed fracture healing in dogs.